The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1116/1.3136864
|View full text |Cite
|
Sign up to set email alerts
|

Study of ion and vacuum ultraviolet-induced effects on styrene- and ester-based polymers exposed to argon plasma

Abstract: Dependence of photoresist surface modifications during plasma-based pattern transfer on choice of feedgas composition: Comparison of C 4 F 8 -and C F 4 -based dischargesPlasma-polymer interactions are important for the purpose of etching, deposition, and surface modification in a wide range of different fields. An Ar discharge from an inductively coupled plasma reactor was used to determine the factors in a simple plasma that control etch and surface roughness behavior for three styrene-based and three ester-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 25 publications
4
65
0
Order By: Relevance
“…[4][5][6][11][12][13][14][15][16] We have previously shown that under energetic Ar + ion bombardment during plasma etching, a dense, amorphous carbonlike modified layer is formed at the surface of a wide range of polymers ͓polystyrene ͑PS͒, poly͑␣-methylstyrene͒, poly͑4-methylstyrene͒, PMMA, poly͑hydroxyadamantyl acrylate͒, and poly͑hydroxyadaman-tyl methacrylate͔͒ with a thickness of a few nanometers. 17 This modified layer forms within the first few seconds of plasma exposure ͑corresponding to an ion fluence ϳ4 ϫ 10 16 cm −2 ͒, concurrent with a period of rapid surface roughening. 17 The bilayer structure formed by ion bombardment in the polymer films is reminiscent of similar bilayer structures composed of a compressed, stiff, thin film constrained to a much softer underlayer, such as SiO 2 ͑Refs.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][11][12][13][14][15][16] We have previously shown that under energetic Ar + ion bombardment during plasma etching, a dense, amorphous carbonlike modified layer is formed at the surface of a wide range of polymers ͓polystyrene ͑PS͒, poly͑␣-methylstyrene͒, poly͑4-methylstyrene͒, PMMA, poly͑hydroxyadamantyl acrylate͒, and poly͑hydroxyadaman-tyl methacrylate͔͒ with a thickness of a few nanometers. 17 This modified layer forms within the first few seconds of plasma exposure ͑corresponding to an ion fluence ϳ4 ϫ 10 16 cm −2 ͒, concurrent with a period of rapid surface roughening. 17 The bilayer structure formed by ion bombardment in the polymer films is reminiscent of similar bilayer structures composed of a compressed, stiff, thin film constrained to a much softer underlayer, such as SiO 2 ͑Refs.…”
Section: Introductionmentioning
confidence: 99%
“…The substantial loss of side-chain methoxycarbonyl groups at high fluences transform PMMA on a disordered polyethylene-like polymer, for which the probability of cross-linking is higher than scission [17,18]. The creation of a dense cross-linked network on the surface of polymers that undergo preferentially chain scission has also been observed under plasma bombardment at high fluences [20].…”
Section: Discussionmentioning
confidence: 95%
“…The fluorescence spectrum of the sample exposed directly to the plasma showed a single broad peak ranging from approximately 500 to 700 nm, while no clear fluorescence peaks were detected from the sample prepared with a synthetic quartz window. Although emission spectrum of low-pressure argon plasma contains many peaks that are dominated by atomic Ar lines in the blue light region (due to 4s-5p transitions) and in the red/near-infrared spectral region (due to 4s-4p transitions) [33,34], few emission lines are emitted in UV and VUV region; resonance lines at 104.8 nm (ArI, 1s 0 -1s 2 ) and 106.7 nm (ArI, 1s 0 -1s 4 ) [10,11,14,16,[34][35][36]. Photon energies of these VUV emission lines are high enough (11.8 and 11.6 eV) to cause breakage of C-C, C-O and C-F bonds in the perfluorocarbon polymer, whose bond energies are 3.60, 3.64 and 4.57 eV, respectively [37].…”
Section: Resultsmentioning
confidence: 99%
“…Compared with other energetic particles in plasma such as ions and electrons, UV photons have a much larger depth of penetration into transparent materials and can induce defects in the bulk region several hundred nanometers below the surface [18][19][20]. In past studies, various analytical methods have been employed for the detection and characterization of plasma-induced damage, including X-ray photoelectron spectroscopy, Fourier transform infrared spectroscopy, and ellipsometry [4,[9][10][11][12][13][14]19,20]. Indeed, these approaches are very useful for studying near-surface damage produced by ion bombardment, but not for detecting very slight damage generated deep in the bulk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation